Wireless attendance identification system based fingerprint - Phang, Ee Zheng (2016)
My project aim is to design an attendance system which could effectively bring more convenience for student. Usually, the attendance is marked after student identification. The identification is based on fingerprint recognition. Fingerprint is one of a kind of biometric identification and it can be considered as a best and fastest method for identification system. This is because they are unique for every person, secure and the most important one is it last of a forever. In this system, it consists of two phase, enrollment and authentication. During enrollment, the user need to place on the fingerprint twice to store the fingerprint data into database wirelessly along with the user’s identity as a template for the subject. During authentication phase, the system will capture the user’s fingerprint and compared it with the template in database to determine a match before attendance is made. The matching process will be shown in GUI system in computer which can display the information of the user. There will be action executed when the authentication is succeeded or failed. The authorized user can also examine the database anytime since the entire students’ attendance will be recorded. Generally, this system is designed to bring more convenience to user by recording attendance in more efficient way with relatively low costs design, ease of installation and also user-friendly interface.